2006
DOI: 10.1253/circj.70.698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preinfarction Angina Pectoris on Myocardial Blush Grade After Reperfusion in First Anterior Wall Acute Myocardial Infarction

Abstract: he presence of preinfarction angina pectoris (PIA) has been shown to have beneficial effects on left ventricular (LV) function and prognosis after acute myocardial infarction (AMI). [1][2][3][4][5][6][7] Recently, myocardial blush grade (MBG) has been shown to be a simple and useful marker of myocardial tissue-level reperfusion in AMI. [8][9][10][11] Because the effect of PIA on MBG has not yet been investigated, we conducted the present study. Methods Study PatientsWe examined 142 consecutive patients (115 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
1
0
1
Order By: Relevance
“…20 Tamura et al demonstrated that the myocardial blush grade was significantly greater in patients with prodromal angina than in those without. 29 Our study results are consistent with their findings. However, the blush grade was significantly smaller in hypertensive patients, suggesting that microcirculatory dysfunction after reperfusion was more evident in patients with hypertension, even those with prodromal angina.…”
Section: Microvascular Circulation and Ischemic Preconditioningsupporting
confidence: 93%
“…20 Tamura et al demonstrated that the myocardial blush grade was significantly greater in patients with prodromal angina than in those without. 29 Our study results are consistent with their findings. However, the blush grade was significantly smaller in hypertensive patients, suggesting that microcirculatory dysfunction after reperfusion was more evident in patients with hypertension, even those with prodromal angina.…”
Section: Microvascular Circulation and Ischemic Preconditioningsupporting
confidence: 93%
“…Влияние ПС на результаты первичной ЧТБКА В настоящее время протективное влияние ПС на течение ИМ у больных, перенесших первичную ЧТБКА, является предметом дискуссий. Данные ряда клинических испытаний продемонстрировали, что при выполнении ЧТБКА наличие ПС было связано с более низкой частотой развития феномена невозобновленного кровотока "no-reflow" [37][38][39]. Положительное влияние ПС у больных, перенесших ЧТБКА, было отмечено не во всех исследованиях [40].…”
Section: взаимосвязь пс с возрастом полом и наличием сопутствующего сдunclassified
“…Pre-infarction angina (PIA) occurring shortly before the onset of AMI has a cardioprotective effect in patients with AMI by the mechanism of ischaemic preconditioning 6 – 8. Moreover, PIA has been shown to preserve microvascular function after reperfusion 912. However, no clinical data exist regarding the influence of acute hyperglycaemia on the relation between PIA and microvascular function after AMI.…”
mentioning
confidence: 99%